2010
DOI: 10.1016/j.surfcoat.2010.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of process parameters on mechanical and tribological performance of pulsed-DC sputtered TiC/a-C:H nanocomposite films

Abstract: Mechanical, structural, chemical bonding (sp 3 /sp 2), and tribological properties of films deposited by pulsed-DC sputtering of Ti targets in Ar/C 2 H 2 plasma were studied as a function of the substrate bias voltage, Ti-target current, C 2 H 2 flow rate and pulse frequency by nanoindentation, Raman spectroscopy and ball-on-disc tribometry. The new findings in this study comprise: dense, column-free, smooth, and ultra-low friction TiC/a-C:H films are obtained at a lower substrate bias voltage by pulsed-DC spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 34 publications
(47 reference statements)
2
17
0
2
Order By: Relevance
“…This in combination with high raw material prices motivates investigations for alternative solutions. While others have studied TiC-based nanocomposites as tribological coatings [2,3,4,5,6,7,8,9], we found that such nanocomposites can function as an electrical contact material [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In our previous works, coatings consisting of nanocrystalline (nc) TiC embedded in an amorphous (a) C or SiC matrix were deposited by dc magnetron sputtering.…”
Section: Introductionmentioning
confidence: 82%
“…This in combination with high raw material prices motivates investigations for alternative solutions. While others have studied TiC-based nanocomposites as tribological coatings [2,3,4,5,6,7,8,9], we found that such nanocomposites can function as an electrical contact material [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In our previous works, coatings consisting of nanocrystalline (nc) TiC embedded in an amorphous (a) C or SiC matrix were deposited by dc magnetron sputtering.…”
Section: Introductionmentioning
confidence: 82%
“…Basically, elastic modulus also plays an important role in determining the wear behavior of material, attributed to that the elastic strain to failure is related to the ratio of hardness (H) and elastic modulus (E). Shaha et al [46] pointed out that the hardness ratio of the tribo-pair and the coating material makes markedly sense on the wear behavior of the coating. When the hardness ratio is above r c1 (0.5-0.8), the wear rate of the counterpart decreases; as the increased hardness ratio is close to r c2 (1-1.4), almost no wear is observed.…”
Section: Discussionmentioning
confidence: 99%
“…As protective coating, transitional metal carbides have lower coefficient of friction (COF) and better wear resistance in comparison with transitional metal nitrides, hence many carbides films with combination of excellent hardness and great tribological behaviors have been extensively investigated such as ZrC, TiC, NbC, WC, etc. [7][8][9][10][11][12]. For instance, the carbon (C) content of ZrC films deposited by Meng et al.…”
Section: Introductionmentioning
confidence: 99%